Thermal-behavior study of chlorine released from composite refuse derived fuel - Song, Zhi-Wei (Waste management (New York, N.Y.), 2009)
In order to reduce secondary pollution during the incineration of composite refuse derived fuel (CRDF), the combustion features and the emission behavior of chlorine in CRDF containing coal were analyzed. The former was analyzed using thermo-gravimetric and the latter by gas chromatography-mass spectrometry. The release rate of inorganic chlorine during combustion reached 90 mass% at temperature between 773.15 and 873.15K. On the other hand, approximately 84 mass% release rates was resulting from pyrolysis at 723.15K. When temperature reached above 1073.15K, it was noticed that higher concentration of organic chlorine in different organic compounds were produced in the processing of pyrolysis compared with those released from the combustion processing. From the thermo-gravimetric analysis using a self-designed system, three distinct phases were detected in the thermal process of CRDF. The first phase occurred at temperature between 473 and 573K and its mass loss was about 38.50%. The second phase between temperature regions of 673-773K with a mass loss of 20.35%. The third phase was observed at the temperature between 873 and 1073K with 22.25% mass loss